Optimizing the Use of Social Media and E-Payment Gateways on MSME Performance - Agustina, Duwi; Yusnita, Maya; Fitari, Tiara (Universitas Bangka Belitung, 2024)
Development and progress of the Indonesian economy has forced the business world to take strategic steps to compete, especially Micro, Small and Medium Enterprises (MSMEs). This study aims to examine the use of social media and the use of e-payment gateways on performance of MSMEs food and beverage sector in Pangkalpinang City which makes it possible to provide convenience in increasing MSME customer loyalty. The method used in this study is a quantitative method, the sample used is MSME in the food and beverage sector, totaling 100 respondents. Data analysis tool used is multiple linear regression test. The results of testing the hypothesis are accepted, which means that social media and e-payment gateway are an innovation capable of reaching customers from various regions, facilitating the dissemination of information and is useful for increasing competitive advantage and maintaining good relations, increasing revenue, increasing sales, and the brand image of business actors.